2017
DOI: 10.23736/s0022-4707.16.06658-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on level of physical activity, depression, anxiety and stress symptoms among adolescents

Abstract: BACKGROUND: Inadequate physical activity has adverse health consequences among adolescents. Mental health problem can be developed by lack of physical activity however it is controversial. The current study aimed to examine the association between level of physical activity with depression, anxiety and stress symptoms among adolescents. METHODS: A representative sample of 1747 adolescents (13-14 years) was randomly selected from 6 schools in a south part of Malaysia. Respondents were asked to fill consent form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…In terms of lifestyle-related factors, the regression analysis demonstrates that not being involved in PA (OR: 1.32) or being involved in irregular PA (OR: 1.30) and doing low PA (OR: 1.22) significantly impact adolescent anxiety, and findings from other studies are also consistent with this finding [45,46]. Studies have demonstrated positive outcomes of PA in relation to anxiety; when adolescents are involved in PA at moderate to high levels, it nullifies anxiety symptoms and disorders.…”
Section: Plos Onesupporting
confidence: 66%
“…In terms of lifestyle-related factors, the regression analysis demonstrates that not being involved in PA (OR: 1.32) or being involved in irregular PA (OR: 1.30) and doing low PA (OR: 1.22) significantly impact adolescent anxiety, and findings from other studies are also consistent with this finding [45,46]. Studies have demonstrated positive outcomes of PA in relation to anxiety; when adolescents are involved in PA at moderate to high levels, it nullifies anxiety symptoms and disorders.…”
Section: Plos Onesupporting
confidence: 66%
“…It shows that the team aerobic exercise intervention program used in this study still has a certain effect on improving the sleep quality of middle school students with depression. Although the results of this study on anxiety and sleep quality are inconsistent with the conclusions of some existing studies ( 26 ), it was speculated that this may be related to the test schedule after the experiment, which is just before the students' final academic assessment. Before facing academic assessment, students may be more prone to anxiety and poor sleep.…”
Section: Discussioncontrasting
confidence: 99%
“…This was akin to the prevalence reported by another local study using CDI (26.2%) in Kuching (the capital city of Sarawak, a state in Malaysia) ( 7 ). Other local studies ( 6 , 8 , 23 , 50 ) also reported similar prevalence but the direct comparison was difficult given the different questionnaires used and the different locations where the studies were conducted.…”
Section: Discussionmentioning
confidence: 95%
“…Physical activity during early adolescence has also been found to predict lower levels of depressive symptoms in later years ( 22 ). Tajik et al ( 23 ) investigated the relationship between physical activity and psychological correlates for example stress, depression, and anxiety, among 1,747 adolescents from the southern part of Malaysia. Their findings showed that level of physical activity was associated with anxiety and stress but not depression ( 23 ).…”
Section: Introductionmentioning
confidence: 99%